Boron nitride-hyperbranched polyimide high-temperature-resistant high-thermal-conductivity insulating impregnating varnish and preparation method thereof
By adopting boron nitride-hyperbranched polyimide high-temperature and high-thermal conductivity insulating impregnated paint, the problem of low thermal conductivity of existing insulating impregnated paint is solved, efficient heat dissipation and insulation safety are achieved, and the demand for new energy vehicle drive motors is met, while reducing production costs.
Patent Information
- Application Number
- CN202411733939.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
The thermal conductivity of existing insulating impregnated paints is relatively low, which is difficult to meet the efficient heat dissipation needs of new energy vehicle drive motors. At the same time, increasing thermal fillers will increase costs and affect the flow performance of the paint.
Boron nitride-hyperbranched polyimide high temperature and high thermal conductivity insulating impregnated paint is used, which is made of hyperbranched polyimide prepolymer, linear polyimide prepolymer, surface modified hexagonal boron nitride, crosslinking agent and strong polar aprotic organic solvent by thermal imidation or chemical imidation reaction.
The thermal conductivity is ≥0.60W·m-1·K-1, the heat resistance level can reach 200 (C level), the thermal weight loss is ≥330℃, and the electrical strength of the industrial frequency is ≥22MV/m, which meets the efficient heat dissipation and insulation safety requirements of future drive motors, while reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of insulating impregnating varnish preparation, and in particular to a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish and a preparation method thereof. Background Art
[0002] Insulating impregnation varnish is mainly used as impregnation insulation for electromagnetic coils such as motor coils and electrical coils, providing good insulation protection function. It is one of the key materials to ensure the operating stability and service life of electrical equipment. With the rapid development of modern science and technology and people's increasing attention to environmental protection issues, new energy vehicles have achieved rapid development and breakthroughs in my country. New energy vehicles are rapidly developing in the direction of "new four modernizations" of electrification, intelligence, networking and sharing. As the core highlight of new energy vehicles, intelligent driving attracts the attention of consumers, and the safety of its intelligent driving is the focus of consumers. Intelligent driving can be explained as the ability of vehicles to make decisions and execute actions based on the perception, analysis and judgment of the surrounding environment, and to achieve automated and intelligent driving through assisted driving, intelligent safety and vehicle intelligent control. The "secret" of intelligent driving lies in the design of the hub motor. Distributed drive electric vehicles based on hub motors highly integrate the drive, braking and steering systems in the drive wheels, achieving a high degree of integration of the chassis system. It can be said that the hub motor in the drive wheel is the best carrier for intelligent driving.
[0003] Due to the complex operating conditions of electric vehicles, limited space in the wheel hub, and difficulty in internal heat dissipation, the motor temperature rises seriously. Excessive temperature will affect the normal operation and service life of the motor, and bring serious harm to the safety of the new energy vehicle. In order to meet the design requirements of the wheel hub motor for intelligent driving, an insulating impregnation paint resin with high temperature resistance and high thermal conductivity is urgently needed.
[0004] However, the thermal conductivity of the existing insulating varnish base resin is relatively low, generally 0.2-0.25 W·m -1 ·K -1 , it needs to be compounded with insulating thermal conductive fillers (such as silicon dioxide SiO2, silicon carbide SiC and aluminum oxide Al2O3, etc.) to improve the overall thermal conductivity of the insulating impregnation varnish to meet the heat dissipation requirements of various new motors and electrical equipment. For example, Wang Yafei, Liu Jing, Fang Hui, etc. published in "Marine Electric Technology" - Preparation and Performance of High Thermal Conductivity Environmentally Friendly Insulating Resins for New Energy Vehicles [J] that the unsaturated polyester imide resin was synthesized by in-situ polymerization. Al2O3 high thermal conductive fillers were mixed in and formulated into high thermal conductivity environmentally friendly insulating resins with a thermal conductivity of 0.45W·m -1 ·K -1 , can be applied to the field of new energy vehicle drive motors.
[0005] The high thermal conductivity and environmentally friendly insulating resin prepared above meets the requirements of high temperature resistance, that is, the heat resistance grade can reach 180 (H grade). Although its thermal conductivity has been improved to a certain extent, it is still lower than 0.6 W·m -1 ·K -1 , it is difficult to meet the timely and efficient heat dissipation requirements of future drive motors. Even if the overall thermal conductivity of the insulating impregnating varnish can be improved by increasing the amount of Al2O3 high thermal conductivity filler, it will not only increase the cost, but also affect the overall flow properties of the insulating impregnating varnish, resulting in the insulating impregnation varnish not meeting the standards, limiting its application development.
[0006] In order to solve the above problems, the inventor provides a method for preparing a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish. Summary of the invention
[0007] In order to meet the timely and efficient heat dissipation requirements of future drive motors, the present application provides a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish and a preparation method thereof.
[0008] In the first aspect, the present application provides a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish, which is achieved by the following technical solutions: A boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is prepared by thermal imidization or chemical imidization reaction of hyperbranched polyimide prepolymer, linear polyimide prepolymer, surface modified hexagonal boron nitride, crosslinking agent and strong polar aprotic organic solvent; the strong polar aprotic organic solvent accounts for 55-70wt% of the whole high temperature resistant and high thermal conductivity insulating impregnation varnish; the added mass of the surface modified hexagonal boron nitride is 50-70wt% of the hyperbranched polyimide prepolymer, linear polyimide prepolymer and surface modified hexagonal boron nitride. The added mass of the hyperbranched polyimide prepolymer is 0.15-0.25 times the total mass of the linear polyimide prepolymer and the surface-modified hexagonal boron nitride; the added mass of the hyperbranched polyimide prepolymer is 0.75-0.90 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer; the added mass of the cross-linking agent is 0.01-0.025 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
[0009] The insulating impregnating varnish provided by the present invention has a heat resistance grade of up to 200 (C grade) and a thermal conductivity coefficient of ≥0.60 W·m -1 ·K -1 , thermal weight loss (calculated as 5% mass loss) ≥330℃, power frequency electrical strength ≥22MV / m, which can meet the timely and efficient heat dissipation and insulation safety requirements of future drive motors.
[0010] Preferably, the added mass of the surface-modified hexagonal boron nitride is 0.18-0.22 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
[0011] Preferably, the added mass of the hyperbranched polyimide prepolymer is 0.80-0.85 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer.
[0012] Preferably, the linear polyimide prepolymer is an anhydride-terminated linear polyamic acid PAA or an amino-terminated linear polyamic acid PAA; the anhydride-terminated linear polyamic acid PAA of the linear polyimide prepolymer is prepared from aromatic diamine and aromatic dianhydride; the molar ratio of the aromatic diamine to the aromatic dianhydride is 2:(1.85-2.2); the aromatic diamine is 4,4'-diaminotriphenyl p-phenylenediamine, 4,4'-diaminotriphenylmethane, 3,5-diaminobenzoic acid-4-(4'-butoxy)biphenyl ester, 3,3'-dimethyl-4 ,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 2,6-diaminopyridine, 4-phenyl-2,6-bis(4-aminophenyl)pyridine; the aromatic dianhydride is at least one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2'-bis-(3,4-dicarboxylic anhydride benzene)hexafluoropropane, 3,3',4,4'-bisphenylsulfonetetracarboxylic dianhydride, 3-bromophthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 2,2-diphenyl-4,4',5,5'-biphenyltetracarboxylic dianhydride.
[0013] Preferably, the hyperbranched polyimide prepolymer is an anhydride-terminated hyperbranched polyamic acid HBPAA; the anhydride-terminated hyperbranched polyamic acid HBPAA is prepared from an aromatic dianhydride A2 monomer and a triamine B3 monomer in a molar ratio of 2:(3.02-3.05); the aromatic dianhydride A2 monomer and the triamine B3 monomer are; the aromatic dianhydride A2 is 2,2-bis[4-(4-maleimide phenoxy)phenyl]propane, 3,3',4,4'-diphenyl sulfide dianhydride, 4,4'-(hexafluoroisopropylene) diphthalide The triamine B3 is at least one of 2,6,14-triaminotriptycene, 2,7,12-triamino-5H-diindole[1,2-a:1',2'-c]fluorene-5,10,15-trione, tris(4-aminophenyl)amine, 1,3,5-tris(4-aminophenoxy)benzene, 4,4',4"-(pyridine-2,4,6-triyl)triphenylamine and 4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine.
[0014] Preferably, the surface-modified hexagonal boron nitride includes at least one of hydroxylation-modified hexagonal boron nitride, amination-modified hexagonal boron nitride, epoxidation-modified hexagonal boron nitride, epoxidation-modified CTNs@h-BN, amination-modified CTNs@h-BN, and hydroxylation-modified CTNs@h-BN.
[0015] By adopting the above technical solution, hexagonal boron nitride can be evenly dispersed in the resin system, thereby ensuring the overall high temperature resistance, insulation safety and good heat dissipation performance, while improving the overall mechanical properties and enhancing the service life and safety of the motor.
[0016] Preferably, the surface-modified hexagonal boron nitride is epoxidation-modified CTNs@h-BN; The preparation method of the surface-modified hexagonal boron nitride is as follows: S1. High temperature activation treatment of h-BN; S2. Weigh 400-600 mL of a 0.02-0.03 mol / L Ag(2E4MI)2Ac complex solution, add 0.5-1.0 parts of CNTs and 0.5-1.0 parts of PVP, disperse by ultrasound for 2-4 hours, add 40-80 parts of h-BN activated in S1, and continue to disperse by ultrasound for 0.5-1.0 hours to obtain a dispersion; S3. The obtained dispersion was subjected to vacuum distillation to remove the organic solvent in the dispersion, and then the solid was sintered at 210-220 ° C for 2-4 hours to obtain a solid; S4. The solid obtained in S3 is ground and crushed by ball milling to obtain CTNs@h-BN ultrafine powder with an average particle size of less than 1000 mesh; S5. The CTNs@h-BN ultrafine powder obtained in S4 is magnetically mixed with a solution of n-butyl lithium, wherein the mass ratio of the n-butyl lithium solution to the CTNs@h-BN ultrafine powder is 1:(50-200), and then an ultrasonic activation reaction is carried out for 1-2 hours. Epichlorohydrin is then added for a nucleophilic substitution reaction, wherein the mass ratio of epichlorohydrin to the CTNs@h-BN ultrafine powder is 1:(4-9). After centrifugation to remove the solvent, the solid product is washed with distilled water and acetone to obtain surface epoxidation-modified CTNs@h-BN.
[0017] The preparation method provided in this application is relatively easy to operate, has good industrialization prospects, and is conducive to reducing production costs.
[0018] Preferably, the surface-modified hexagonal boron nitride is a hyperbranched polyimide graft-modified h-BN ultrafine powder or a hyperbranched polyimide graft-modified CTNs@h-BN ultrafine powder; The preparation method of the surface-modified hexagonal boron nitride is as follows: S1. Preparation of h-BN carrier, the h-BN carrier is h-BN ultrafine powder or CTNs@h-BN ultrafine powder; S2. The h-BN carrier and an aqueous solution of aminosilane with a concentration of 4-8wt% are mixed uniformly in a mass ratio of 1:(10-20), and then ultrasonic dispersion treatment is performed for 1-2h, and then filtered and dried to obtain an aminosilane-modified h-BN carrier; S3. Dispersing the aminosilane-modified h-BN carrier in a highly polar aprotic organic solvent to form a suspension, wherein the content of the aminosilane-modified h-BN carrier in the suspension is 0.5-2wt%; adding ternary anhydride to the suspension, adding triethylamine as a catalyst after sufficient dissolution, heating to 40° C., and reacting for 0.5-1h under ultrasonic dispersion conditions, wherein the amino groups on the surface of the h-BN carrier participate in a nucleophilic addition reaction, and undergo a ring-opening reaction with the anhydride group in the ternary anhydride, wherein at least one anhydride in the ternary anhydride is chemically bonded to the aminosilane-modified h-BN carrier; S4. Adding an aromatic diamine, wherein the molar ratio of the aromatic diamine to the ternary anhydride is 2:(1-1.3), maintaining the temperature at 40° C. and reacting for 12-18 hours under ultrasonic dispersion, and then adding maleic anhydride for end-capping, wherein the molar ratio of maleic anhydride to the aromatic diamine is (0.2-0.5):1, maintaining the temperature at 40° C. and reacting for 8-12 hours under ultrasonic dispersion to obtain an ultrafine polyamic acid HBPAA with h-BN as the core; S5. Add an excess of imidizing agent dropwise into the reaction system, wherein the imidizing agent is a mixture of acetic anhydride and triethylamine in a molar ratio of 1:(0.8-1.2), maintain nitrogen protection, and perform ultrasonic dispersion at room temperature for 8-12 hours to obtain a polymer solution. The obtained polymer solution is precipitated into methanol, stirred and washed, and dried in a vacuum oven for 6-8 hours to obtain hyperbranched polyimide grafted modified h-BN or hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder.
[0019] The preparation method provided in this application is relatively easy to operate, has good industrialization prospects, and is conducive to reducing production costs.
[0020] Preferably, the highly polar aprotic organic solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and N,N-dimethylformamide; the cross-linking agent is at least one of tetraphenol ethane type epoxy resin, glycidyl ether epoxy resin, hyperbranched polyimide epoxy resin, triglycidyl meta-aminophenol, small molecule diamine, and small molecule triamine.
[0021] By adopting the above technical solution,
[0022] In the second aspect, the present application provides a method for preparing a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish, which is achieved by the following technical scheme: A method for preparing a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish comprises the following steps: Step 1, respectively preparing a hyperbranched polyimide prepolymer, a linear polyimide prepolymer, and a surface-modified hexagonal boron nitride; Step 2: dissolving the hyperbranched polyimide prepolymer, linear polyimide prepolymer and surface-modified hexagonal boron nitride prepared in step 1 in a highly polar aprotic organic solvent, stirring them magnetically and then degassing them in vacuum to obtain a high temperature resistant and highly thermally conductive insulating impregnation varnish material A; Step 3, evenly mix the high temperature resistant and high thermal conductivity insulating impregnating varnish material A and the cross-linking agent material B to obtain a finished high temperature resistant and high thermal conductivity insulating impregnating varnish; The impregnation conditions of the finished product of high-temperature resistant and high-thermal conductive insulating impregnation varnish are as follows: after the motor is impregnated, it is placed in a vacuum oven and maintained at a temperature of 25-40°C for drying for 1-2 hours, and vibrates for 3-5 seconds every 10-30 seconds during the drying period; then the temperature is raised to 160-180°C and maintained for 1-2 hours to heat and remove the organic solvent in the insulating impregnation varnish, and then the temperature is raised to 220-260°C for insulation treatment for 1-2 hours, and finally heated to 240-280°C for heat treatment and curing for 2-6 hours.
[0023] In summary, this application has the following advantages: 1. The insulation impregnation varnish provided by the present invention has a heat resistance grade of up to 200 (C grade) and a thermal conductivity coefficient of ≥0.60W·m -1 ·K -1 , thermal weight loss (calculated as 5% mass loss) ≥330℃, power frequency electrical strength ≥22MV / m, which can meet the timely and efficient heat dissipation and insulation safety requirements of future drive motors.
[0024] 2. The preparation method provided by the present invention is relatively simple and easy to realize industrialized manufacturing, thereby reducing the production cost and use cost of the insulating impregnating varnish and promoting the development and breakthrough of new energy vehicles. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0026] Preparation Example 1: The preparation method of hydroxylated modified hexagonal boron nitride is as follows: Step 1, placing the purchased submicron ultrafine boron nitride powder (average particle size 600nm, CW-BN-002, hexagonal crystal form, Shanghai Chaowei Nano) in a planetary ball mill for fine ball milling treatment, ball milling at 80rpm for 30min, and set aside; Step 2, mixing potassium hydroxide and sodium hydroxide in a mass ratio of 1:1 and grinding into powder to obtain a mixed powder; Step 3, mixing the mixed powder with hexagonal boron nitride powder and placing it in an autoclave at 190°C to react for 1.5h, the mass ratio of the mixed powder obtained in step 2 to the hexagonal boron nitride powder obtained in step 1 is 4:1, and after the reaction is completed, the reaction product is filtered, centrifuged, and dried to obtain surface hydroxylated boron nitride.
[0027] Preparation Example 2: The preparation method of amino-modified hexagonal boron nitride is as follows: 2 g of purchased submicron ultrafine boron nitride powder (average particle size 600 nm, CW-BN-002, hexagonal crystal, Shanghai Chaowei Nano) is placed in a reactor with a microwave generator, and the reactor is evacuated to a pressure between 0.1-0.5 Pa, and then 30 sccm of ammonia is introduced into the reactor. Aminated boron nitride can be obtained by microwave treatment for 30 minutes.
[0028] Preparation Example 3: The preparation method of amino-modified hexagonal boron nitride is as follows: Step 1, prepare an aqueous solution of aminosilane with a concentration of 4.0wt%, and mix 4g of γ-aminopropyltriethoxysilane KH550 with 996 deionized water; Step 2, weigh 10g of the surface hydroxylated boron nitride prepared in Preparation Example 1 and put it into 500mL of a 4.0wt% γ-aminopropyltriethoxysilane KH550 aqueous solution, first stir it magnetically at 200rpm for 5min, and then perform ultrasonic dispersion treatment, the ultrasonic frequency is 40kHz / power is 600W, after ultrasonic treatment for 30min, filter under reduced pressure, and place the obtained solid in a vacuum drying oven, and dry it at 105°C for 4h under an internal pressure of 10Pa to obtain a solid material; Step 3, the solid material obtained in step 2 is placed in a planetary ball mill for fine ball milling treatment, and the speed is 60rpm for ball milling for 45min to obtain amino-modified hexagonal boron nitride.
[0029] Preparation Example 4: The preparation method of epoxy-modified hexagonal boron nitride is as follows: Step 1, prepare an epoxy silane aqueous solution with a concentration of 5wt%, and mix 5g of γ-glycidyloxypropyltrimethylsilyl KH560 with 995 deionized water to obtain a solid; Step 2, weigh 10g of the surface hydroxylated boron nitride prepared in Preparation Example 1 and put it into 500mL of a 5wt% γ-aminopropyltriethoxysilane KH550 aqueous solution, first stir it magnetically at 200rpm for 5min, and then perform ultrasonic dispersion treatment, the ultrasonic frequency is 40kHz / power is 600W, after ultrasonic treatment for 30min, filter under reduced pressure, and place the obtained solid in a vacuum drying oven, and dry it at 105°C for 4h under an internal pressure of 10Pa to obtain a solid material; Step 3, the solid material obtained in step 2 is placed in a planetary ball mill for fine ball milling treatment, and the speed is 60rpm for ball milling for 45min to obtain epoxy-modified hexagonal boron nitride.
[0030] Preparation Example 5: The preparation method of hydroxylated modified CTNs@h-BN is as follows: S1. Activate h-BN at high temperature: Place the purchased submicron ultrafine boron nitride powder (average particle size 600nm, CW-BN-002, hexagonal crystal, Shanghai Chaowei Nano) in an oven for activation treatment at 160°C for 2h, and then place it in a planetary ball mill for fine ball milling at 80rpm for 30min; At the same time, prepare the Ag(2E4MI)2Ac complex solution: At room temperature, add 0.02mol of 2-ethyl-4-methylimidazole 2E4MI and 0.01 mol of silver acetate AgAc were added to 400 mL of dichloromethane and stirred magnetically at a speed of 240 r / min until the AgAc particles completely disappeared to obtain a clear and transparent Ag(2E4MI)2Ac complex solution; S2. To the Ag(2E4MI)2Ac complex solution prepared in S1, 0.5 g of CNTs (industrial grade multi-walled carbon nanotubes IMWCNTs, model TNIM3, OD: 10-20 nm, length 20-100 microns, Chinese Academy of Sciences) was added. Chengdu Organic Chemistry Co., Ltd.), 0.5g of polyvinyl pyrrolidone PVP, ultrasonic dispersion treatment, ultrasonic frequency 40kHz / power 600W, ultrasonic dispersion treatment for 3 hours, add 50g of h-BN activated in S1 and continue ultrasonic dispersion for 0.5 hours to obtain a dispersion; S3. The obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent-dichloromethane in the dispersion, and then the solid is sintered at 210°C for 4 hours to obtain a solid; S4. The solid obtained in S3 is placed in a three-roll mill for three grinding and crushing treatments, and the roller distance of the three-roll mill is 2 0μm, and after grinding and crushing, the separation is introduced into a planetary ball mill for ball milling and refining, and the rotation speed is 60rpm for 60min to obtain CTNs@h-BN ultrafine powder with an average particle size of 200-250nm; S5. The CTNs@h-BN ultrafine powder is placed in a plasma surface treatment instrument, and ozone is introduced at 0-4℃ for low-temperature plasma treatment for 8min, the plasma generator frequency is 40KHz, and the gas flow rate under the float needle valve flow controller is 0.6L / min, so as to obtain surface hydroxylated modified CTNs@h-BN ultrafine powder.
[0031] The difference between Preparation Example 6 and Preparation Example 5 is: Preparation of amino-modified CTNs@h-BN ultrafine powder, the difference in the specific preparation method is, S5. Place the CTNs@h-BN ultrafine powder in a plasma surface treatment instrument, and introduce nitrogen at 0-4°C for low-temperature plasma treatment for 8 minutes. The plasma generator frequency is 40KHz, and the gas flow rate under the float needle valve flow controller is 1L / min, so as to obtain surface amino-modified CTNs@h-BN ultrafine powder.
[0032] The difference between Preparation Example 7 and Preparation Example 5 is: preparing amino-modified CTNs@h-BN ultrafine powder, the difference in the specific preparation method is, S5. Place the CTNs@h-BN ultrafine powder in a reactor with a microwave generator, and evacuate the reactor to a pressure between 0.1-0.5Pa, and then introduce 30sccm of ammonia into the reactor, and microwave treatment for 30min to obtain the amino-modified CTNs@h-BN ultrafine powder.
[0033] Preparation Example 8 is different from Preparation Example 5 in that: epoxidized modified CTNs@h-BN ultrafine powder is prepared, and the specific preparation method is different in that: S5. Prepare a 5wt% epoxysilane aqueous solution, mix 5g of γ-glycidyloxypropyltrimethylsilane KH560 with 995 deionized water; weigh 10g of the CTNs@h-BN ultrafine powder prepared in Preparation Example 5 and add 500mL of 5wt% γ-aminopropyltriethoxysilane KH55 0 aqueous solution, first stirred magnetically at 200 rpm for 5 min, then subjected to ultrasonic dispersion treatment, ultrasonic frequency 40 kHz / power 600 W, ultrasonic treatment for 30 min, and then filtered under reduced pressure. The obtained solid was placed in a vacuum drying oven and dried at 105 ° C for 4 h under an internal pressure of 10 Pa to obtain a solid material. The obtained solid material was placed in a planetary ball mill for fine ball milling treatment at a speed of 60 rpm for 45 min to obtain epoxidized modified CTNs@h-BN ultrafine powder.
[0034] The difference between Preparation Example 9 and Preparation Example 1 is that the preparation of hyperbranched polyimide grafted modified h-BN is as follows: first, 2g of amino-modified hexagonal boron nitride in Preparation Example 3 is dispersed in 200ml of a strongly polar aprotic organic solvent - N-methylpyrrolidone NMP to form a suspension, and then 0.004mol of phosphorus-containing trianhydride monomer (synthesized by the preparation method of phosphorus-containing trianhydride monomer in Preparation Example 1 in reference to the phosphorus-containing trianhydride monomer and its preparation method disclosed in Announcement No. CN118221734A) is added to the suspension. After fully dissolved, 0.02g of triethylamine is added as a catalyst, the temperature is raised to 40°C, and the reaction is carried out under ultrasonic dispersion conditions (ultrasonic frequency 40kHz / power 600W) for 1h. The amino group on the surface of the h-BN carrier participates in the nucleophilic addition reaction and undergoes a ring-opening reaction with the anhydride group in the phosphorus-containing trianhydride monomer. At least one of the anhydrides in the ternary anhydride is chemically bonded to the aminosilane-modified h-BN carrier; 0.008 mol of 3,3'-dimethyl-4,4'-diaminodiphenylmethane is added, maintained at 40°C and reacted for 12 hours under ultrasonic dispersion, then 0.004 mol of maleic anhydride is added for end-capping, maintained at 40°C and reacted for 12 hours under ultrasonic dispersion to obtain ultrafine polyamic acid HBPAA with h-BN as the core, 12 ml of an excess imidization agent is added dropwise to the reaction system, the imidization agent is a mixture of acetic anhydride and triethylamine in a molar ratio of 1:1, nitrogen protection is maintained, ultrasonic dispersion is performed at room temperature for 12 hours to obtain a polymer solution, the obtained polymer solution is precipitated into methanol, stirred and washed, and dried in a vacuum oven for 8 hours to obtain a hyperbranched polyimide grafted modified h-BN ultrafine powder.
[0035] The difference between Preparation Example 10 and Preparation Example 9 is that 2 g of the surface amino-modified CTNs@h-BN ultrafine powder in Preparation Example 6 is dispersed in 200 ml of a strongly polar aprotic organic solvent, N-methylpyrrolidone NMP, to form a suspension, thereby finally obtaining a hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder. Example
[0036] A boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is prepared from hyperbranched polyimide prepolymer, linear polyimide prepolymer, surface modified hexagonal boron nitride, a crosslinking agent and a highly polar aprotic organic solvent through thermal imidization or chemical imidization reaction.
[0037] The highly polar aprotic organic solvent is one or a combination of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide.
[0038] The highly polar aprotic organic solvent accounts for 55-70wt% of the total high temperature resistant and high thermal conductivity insulating impregnation varnish.
[0039] The added mass of the surface-modified hexagonal boron nitride is 0.15-0.25 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
[0040] Preferably, the added mass of the surface-modified hexagonal boron nitride is 0.18-0.22 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
[0041] The added mass of the hyperbranched polyimide prepolymer is 0.75-0.90 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer.
[0042] Preferably, the added mass of the hyperbranched polyimide prepolymer is 0.80-0.85 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer.
[0043] The crosslinking agent is at least one of tetraphenol ethane type epoxy resin, glycidyl ether epoxy resin, hyperbranched polyimide epoxy resin, triglycidyl meta-aminophenol, small molecule diamine and small molecule triamine.
[0044] Preferably, the cross-linking agent is a hyperbranched polyimide-based epoxy resin.
[0045] The added mass of the cross-linking agent is 0.01-0.025 times of the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
[0046] The linear polyimide prepolymer is an anhydride-terminated linear polyamic acid PAA or an amino-terminated linear polyamic acid PAA. The anhydride-terminated linear polyimide prepolymer PAA is prepared from aromatic diamine and aromatic dianhydride.
[0047] The molar ratio of the aromatic diamine to the aromatic dianhydride is 2:(1.85-2.2); the aromatic diamine is at least one of 4,4'-diaminotriphenyl-p-phenylenediamine, 4,4'-diaminotriphenylmethane, 3,5-diaminobenzoic acid-4-(4'-butoxy)biphenyl ester, 3,3'-dimethyl-4,4'diaminodiphenylmethane, 4,4'-diaminobenzanilide, 2,6-diaminopyridine, and 4-phenyl-2,6-bis(4-aminophenyl)pyridine.
[0048] The aromatic dianhydride is at least one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2'-bis-(3,4-dicarboxylic anhydride benzene)hexafluoropropane, 3,3',4,4'-bisphenylsulfonetetracarboxylic dianhydride, 3-bromopyrophthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride and 2,2-diphenyl-4,4',5,5'-biphenyltetracarboxylic dianhydride.
[0049] The hyperbranched polyimide prepolymer is an anhydride-terminated hyperbranched polyamic acid HBPAA.
[0050] Anhydride-terminated hyperbranched polyamic acid HBPAA is prepared from aromatic dianhydride A2 monomer and triamine B3 monomer 2:(3.02-3.05).
[0051] The molar amounts of the aromatic dianhydride A2 monomer and the triamine B3 monomer are as follows: the aromatic dianhydride A2 is at least one of 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3',4,4'-diphenyl sulfide dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, and 3,3,4,4-diphenyl sulfone tetracarboxylic dianhydride.
[0052] The triamine B3 is at least one of 2,6,14-triaminotriptycene, 2,7,12-triamino-5H-diindole[1,2-a:1',2'-c]fluorene-5,10,15-trione, tris(4-aminophenyl)amine, 1,3,5-tris(4-aminophenoxy)benzene, 4,4',4"-(pyridine-2,4,6-triyl)triphenylamine, and 4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine.
[0053] The surface-modified hexagonal boron nitride includes at least one of hydroxylation-modified hexagonal boron nitride, amination-modified hexagonal boron nitride, epoxidation-modified hexagonal boron nitride, epoxidation-modified CTNs@h-BN, amination-modified CTNs@h-BN, and hydroxylation-modified CTNs@h-BN.
[0054] Preferably, the surface-modified hexagonal boron nitride is epoxidation-modified CTNs@h-BN.
[0055] The preparation method of surface-modified hexagonal boron nitride, i.e., epoxidation-modified CTNs@h-BN, is as follows: S1. High temperature activation treatment of h-BN; S2. Weigh 400-600 mL of a 0.02-0.03 mol / L Ag(2E4MI)2Ac complex solution, add 0.5-1.0 parts of CNTs and 0.5-1.0 parts of PVP, disperse by ultrasound for 2-4 hours, add 40-80 parts of h-BN activated in S1, and continue to disperse by ultrasound for 0.5-1.0 hours to obtain a dispersion; S3. The obtained dispersion was subjected to vacuum distillation to remove the organic solvent in the dispersion, and then the solid was sintered at 210-220 ° C for 2-4 hours to obtain a solid; S4. The solid obtained in S3 is ground and crushed by ball milling to obtain CTNs@h-BN ultrafine powder with an average particle size of less than 1000 mesh; S5. The CTNs@h-BN ultrafine powder obtained in S4 is magnetically mixed with a solution of n-butyl lithium, the mass ratio of the solution of n-butyl lithium to the CTNs@h-BN ultrafine powder is 1:(50-200), and then an ultrasonic activation reaction is carried out for 1-2 hours, and then epichlorohydrin is added for a nucleophilic substitution reaction, the mass ratio of epichlorohydrin to the CTNs@h-BN ultrafine powder is 1:(4-9). After centrifugation to remove the solvent, the solid product is washed with distilled water and acetone to obtain surface epoxidation-modified CTNs@h-BN.
[0056] Preferably, the surface-modified hexagonal boron nitride is a hyperbranched polyimide graft-modified h-BN ultrafine powder or a hyperbranched polyimide graft-modified CTNs@h-BN ultrafine powder. The preparation method of the surface-modified hexagonal boron nitride is as follows: S1. Preparation of h-BN carrier, the h-BN carrier is h-BN ultrafine powder or CTNs@h-BN ultrafine powder; S2. The h-BN carrier and an aqueous solution of aminosilane with a concentration of 4-8wt% are mixed uniformly in a mass ratio of 1:(10-20), and then ultrasonic dispersion treatment is performed for 1-2h, and then filtered and dried to obtain an aminosilane-modified h-BN carrier; S3. Dispersing the aminosilane-modified h-BN carrier in a highly polar aprotic organic solvent to form a suspension, wherein the content of the aminosilane-modified h-BN carrier in the suspension is 0.5-2wt%; adding ternary anhydride to the suspension, adding triethylamine as a catalyst after sufficient dissolution, heating to 40°C, and reacting for 0.5-1h under ultrasonic dispersion conditions, wherein the amino groups on the surface of the h-BN carrier participate in a nucleophilic addition reaction, and undergo a ring-opening reaction with the anhydride group in the ternary anhydride, wherein at least one anhydride in the ternary anhydride is chemically bonded to the aminosilane-modified h-BN carrier; S4. Add aromatic diamine, the molar ratio of aromatic diamine to ternary anhydride is 2: (1-1.3), maintain at 40 ° C and react under ultrasonic dispersion for 12-18h, then add maleic anhydride for end-capping, the molar ratio of maleic anhydride to aromatic diamine is (0.2-0.5): 1, maintain at 40 ° C and react under ultrasonic dispersion for 8-12h to obtain ultrafine polyamic acid HBPAA with h-BN as the core; S5. Add an excess of imidizing agent dropwise into the reaction system, wherein the imidizing agent is a mixture of acetic anhydride and triethylamine in a molar ratio of 1:(0.8-1.2), maintain nitrogen protection, and perform ultrasonic dispersion at room temperature for 8-12 hours to obtain a polymer solution. The obtained polymer solution is precipitated into methanol, stirred and washed, and dried in a vacuum oven for 6-8 hours to obtain hyperbranched polyimide grafted modified h-BN or hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder.
[0057] The preparation method of boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish comprises the following steps: Step 1, respectively preparing a hyperbranched polyimide prepolymer, a linear polyimide prepolymer, and a surface-modified hexagonal boron nitride; Step 2: dissolving the hyperbranched polyimide prepolymer, linear polyimide prepolymer and surface-modified hexagonal boron nitride prepared in step 1 in a highly polar aprotic organic solvent, stirring them magnetically and then degassing them in vacuum to obtain a high temperature resistant and highly thermally conductive insulating impregnation varnish material A; Step 3, evenly mix the high temperature resistant and high thermal conductivity insulating impregnating varnish material A and the cross-linking agent material B to obtain a finished high temperature resistant and high thermal conductivity insulating impregnating varnish; The impregnation conditions of the finished high-temperature resistant and high thermal conductivity insulating impregnation varnish are as follows: After impregnation, the motor is placed in a vacuum oven and maintained at 25-40°C for 1-2 hours. During the drying period, vibrate for 3-5 seconds every 10-30 seconds; then heat to 160-180°C and maintain for 1-2 hours to remove the organic solvent in the insulating impregnation varnish, then heat to 220-260°C for insulation treatment for 1-2 hours, and finally heat to 240-280°C for heat treatment and curing for 2-6 hours.
[0058] Example 1: A boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 24.8wt% of hyperbranched polyimide prepolymer, 6.2wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0059] The preparation method of boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish comprises the following steps: Step 1, respectively preparing a hyperbranched polyimide prepolymer, a linear polyimide prepolymer, and a surface-modified hexagonal boron nitride; The surface-modified hexagonal boron nitride is prepared by referring to the preparation of the surface-hydroxyl-modified hexagonal boron nitride in Preparation Example 1; The preparation method of the linear polyimide prepolymer is as follows: in a completely dry 500 mL straight four-necked flask equipped with a water separator, 200 ml of N-methylpyrrolidone NMP and 100 ml of dimethyl sulfoxide DMSO are added after nitrogen protection, and then 0.01 mol (2.74 g) of 4,4'-diaminotriphenylmethane (CAS No. 603-40-7, molecular weight 274.36) is added and fully dissolved. At 25°C, magnetic stirring is maintained at 120 rpm and under N2 protection, magnetic stirring is maintained for 5 min, and then 0.01 mol (2.94 g) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (CAS No. 2420-87-3, molecular weight 294.215) is added, and the water bath is heated to 40°C to accelerate the initiation reaction, and magnetic stirring is maintained for 12 hours, and 0.0001 mol (0.27 g) of 4,4'-diaminotriphenylmethane was used for end-capping, and after magnetic stirring for 12 h, the amino-terminated linear polyimide prepolymer, namely PAA, was obtained; The preparation method of the hyperbranched polyimide prepolymer is as follows: in a completely dry 500 mL straight four-necked flask equipped with a water separator, 200 ml of N-methylpyrrolidone NMP and 100 ml of dimethyl sulfoxide DMSO are added after nitrogen protection, and then 0.01 mol (3.52 g) of 4,4',4"-(pyridine-2,4,6-triyl)triphenylamine (CAS No.: 83266-97-1 molecular weight 352.43) is added. After 4,4',4"-(pyridine-2,4,6-triyl)triphenylamine is fully dissolved, the mixture is stirred at 25°C for 5 minutes under 120 rpm magnetic stirring and N2 protection. After 15 min, 0.015 mol (6.67 g) of 4,4'-(hexafluoroisopropylene) diphthalic anhydride (CAS No. 1107-00-2, molecular weight 444.238) was added, and the reaction was accelerated by heating in a water bath to 40°C, and magnetic stirring was maintained for 16 h. 0.001 mol (0.45 g) of 4,4'-(hexafluoroisopropylene) diphthalic anhydride was added for end-capping, and magnetic stirring was performed for 12 h to obtain anhydride-terminated hyperbranched polyimide prepolymer, namely HBPAA. Step 2: evenly mix the hyperbranched polyimide prepolymer and the linear polyimide prepolymer prepared in step 1, add surface hydroxyl-modified hexagonal boron nitride and N-methylpyrrolidone, control the solid content of the liquid material to 40wt%, stir evenly with a magnetic stirrer, and then vacuum degasse to obtain a high temperature resistant and high thermal conductivity insulating impregnation paint A material; Step 3, 99 parts by mass of high temperature resistant and high thermal conductivity insulating impregnating varnish material A and 1 part by mass of cross-linking agent material B are magnetically stirred to obtain a finished product of high temperature resistant and high thermal conductivity insulating impregnating varnish; The impregnation conditions of the finished high-temperature resistant and high thermal conductivity insulating impregnation varnish are as follows: After impregnation, the motor is placed in a vacuum oven and maintained at 40°C for 1 hour, with vibration for 5 seconds every 30 seconds during the drying period; then the temperature is raised to 180°C and maintained for 1 hour to remove the organic solvent in the insulating impregnation varnish, then the temperature is raised to 240°C and kept for 2 hours, and finally heated to 265°C for heat treatment and curing for 2 hours.
[0060] The difference between Example 2 and Example 1 is that the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 26.4wt% of hyperbranched polyimide prepolymer, 6.6wt% of linear polyimide prepolymer, 6wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0061] The difference between Example 3 and Example 1 is that the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 23.2wt% of hyperbranched polyimide prepolymer, 5.8wt% of linear polyimide prepolymer, 10wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0062] The difference between Example 4 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 23.25wt% of hyperbranched polyimide prepolymer, 7.75wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0063] The difference between Example 5 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 27.9wt% of hyperbranched polyimide prepolymer, 3.1wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0064] The difference between Example 6 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 25.28wt% of hyperbranched polyimide prepolymer, 6.32wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 0.4wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0065] The difference between Example 7 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 25.2wt% of hyperbranched polyimide prepolymer, 6.30wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 0.5wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0066] The difference between Example 8 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 25.28wt% of hyperbranched polyimide prepolymer, 6.32wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 0.4wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0067] The difference between Example 9 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by the hexagonal boron nitride with surface amino modified in Preparation Example 2.
[0068] The difference between Example 10 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by the hexagonal boron nitride with surface amino modified in Preparation Example 3.
[0069] The difference between Example 11 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by the hexagonal boron nitride with surface epoxy modified in Preparation Example 4.
[0070] The difference between Example 12 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by CTNs@h-BN with surface hydroxyl modified in Preparation Example 5.
[0071] The difference between Example 13 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by CTNs@h-BN with surface amino modified in Preparation Example 6.
[0072] The difference between Example 14 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by CTNs@h-BN with surface amino modified in Preparation Example 7.
[0073] The difference between Example 15 and Example 1 is that the hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1 is replaced by CTNs@h-BN with surface epoxidation modified in Preparation Example 8.
[0074] The difference between Example 16 and Example 1 is that the hexagonal boron nitride with surface hydroxyl groups modified in Preparation Example 1 is replaced by the hyperbranched polyimide grafted modified h-BN ultrafine powder in Preparation Example 9.
[0075] The difference between Example 17 and Example 1 is that the hexagonal boron nitride with surface hydroxyl groups modified in Preparation Example 1 is replaced by the hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder in Preparation Example 10.
[0076] The difference between Example 18 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 24.8wt% of hyperbranched polyimide prepolymer, 6.2wt% of linear polyimide prepolymer, 7.8wt% of the surface hydroxyl-modified hexagonal boron nitride in Preparation Example 1, 0.2wt% of the surface hydroxyl-modified boron nitride whiskers, 1.0wt% of the cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0077] The preparation method of surface hydroxyl-modified boron nitride whiskers is as follows: first, potassium hydroxide and sodium hydroxide are mixed in a mass ratio of 1:1 and ground into powder to obtain a mixed powder, and then the mixed powder is mixed with boron nitride whiskers (diameter 0.5 μm, length 20 μm, Shanghai Xiangtian Nanomaterials Co., Ltd.) and placed in a 190°C autoclave for reaction for 1.5 hours. The mass ratio of the mixed powder to the boron nitride whiskers is 4:1. After the reaction is completed, the reaction product is filtered, centrifuged, and dried to obtain surface hydroxylated boron nitride whiskers.
[0078] The difference between Example 19 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 24.8wt% of hyperbranched polyimide prepolymer, 6.2wt% of linear polyimide prepolymer, 7.8wt% of the surface hydroxyl-modified hexagonal boron nitride in Preparation Example 1, 0.2wt% of the surface hydroxyl-modified CTNs@boron nitride whiskers, 1.0wt% of the cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0079] The preparation method of CTNs@boron nitride whiskers with surface hydroxyl modification is as follows: S1. Boron nitride whiskers (diameter 0.5 μm, length 20 μm, Shanghai Xiangtian Nanomaterials Co., Ltd.) are first placed in an oven for activation treatment at 160°C for 2 hours, and then placed in a planetary ball mill for ball milling dispersion treatment at a speed of 30 rpm for 10 minutes; at the same time, Ag(2E4MI)2Ac complex solution is prepared: at room temperature, 0.02 mol of 2-ethyl-4-methylimidazole 2E4MI and 0.01 mol of silver acetate A are added. 1. Add 0.5 g of CNTs (industrial grade multi-walled carbon nanotubes IMWCNTs, model TNIM3, OD: 10-20 nm, length 20-100 microns, Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences) to the Ag(2E4MI)2Ac complex solution prepared in S1. Co., Ltd.), 0.5g of polyvinyl pyrrolidone PVP, ultrasonic dispersion treatment, ultrasonic frequency 40kHz / power 600W, ultrasonic dispersion treatment for 3 hours, add 50g of h-BN whiskers activated in S1 and continue ultrasonic dispersion for 0.5 hours to obtain a dispersion; S3. The obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent-dichloromethane in the dispersion, and then the solid is sintered at 210°C for 4 hours to obtain a solid; S4. The solid obtained in S3 is placed in a three-roll mill and ground and crushed three times, three The roller spacing of the roller mill is 20 μm. The separation after grinding and crushing is introduced into a planetary ball mill for ball milling and refining. The rotation speed is 30 rpm and the ball milling is carried out for 30 minutes to obtain CTNs@h-BN whisker powder; S5. The CTNs@h-BN whisker powder is placed in a plasma surface treatment instrument, and ozone is introduced at 0-4°C for low-temperature plasma treatment for 8 minutes. The frequency of the plasma generator is 40 KHz, and the gas flow rate under the float needle valve flow controller is 0.6 L / min, so as to obtain surface hydroxylated modified CTNs@h-BN whiskers.
[0080] The difference between Example 20 and Example 19 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 24.8wt% of a hyperbranched polyimide prepolymer, 6.2wt% of a linear polyimide prepolymer, 7.8wt% of the hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder in Preparation Example 10, 0.2wt% of surface hydroxyl-modified CTNs@boron nitride whiskers, 1.0wt% of a cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0081] The difference between Example 21 and Example 1 is that the cross-linking agent, triglycidyl-m-aminophenol, is replaced by tris(4-aminophenyl)amine (CAS No.: 5981-09-9).
[0082] The difference between Example 22 and Example 1 is that the cross-linking agent - triglycidyl meta-aminophenol is replaced by 1,1,2,2-tetra-p-hydroxyphenylethane tetraglycidyl ether epoxy resin (synthesized according to the document "Synthesis of Tetraphenolethane Tetraglycidyl Ether Epoxy Resin - Peng Hongxing").
[0083] The synthesis method of 1,1,2,2-tetra-p-hydroxyphenylethane tetraglycidyl ether epoxy resin is as follows: Synthesis of tetraphenol ethane product: In a 1000mL four-necked bottle with stirring, condenser, thermometer and feeding funnel, nitrogen is introduced to replace the air in the bottle, 40% glyoxal aqueous solution and methanol are added in proportion, stirring is started, water is condensed, and then phenol is slowly added, stirred evenly, and the temperature is raised to 82°C. Add an appropriate amount of catalyst, control the reaction temperature at about 82°C, and the reaction heat should be removed in time during the reaction. The tetraphenol ethane (TPE) is obtained by reacting for 8 hours. After the condensation reaction is completed, the tetraphenol ethane mixture solution generated by the reaction is neutralized with sodium hydroxide solution, and the amount used is the chemical equivalent of the acid catalyst, and then the precipitated salt and filter residue are removed by filtration. The filtrate is evaporated to remove water, methanol and phenol at a temperature of 180-190°C and a vacuum degree of 0.004Mpa. The removed methanol and phenol are condensed and recycled in sections for repeated use. The filtrate after the solvent is removed is cooled to obtain a brown solid tetraphenol ethane crude product, and then the tetraphenol ethane crude product is refined. Add 400 mL of acetone to the crude mixture, heat and dissolve under stirring, and after the product is completely dissolved, filter the solid-liquid separation salt, and distill off the solvent to obtain a tetraphenol ethane compound. Repeat the same operation three times to obtain a tetraphenol ethane product with a certain purity; Synthesis of 1,1,2,2-tetra-p-hydroxyphenylethane tetraglycidyl ether epoxy resin (PGEE): First, nitrogen was introduced into a 1L four-necked bottle with a stirrer, a thermometer and a condensation reflux device to replace the air, then 245g of ECH was added to the four-necked bottle, stirring and condensing water were turned on, and then an appropriate amount of TEP and 45g of isopropanol were added, and the temperature was raised to dissolve TEP; 4.2g of tetraethylammonium bromide was added to react at 85°C for etherification for 4h; then the reaction temperature was controlled to 70°C, and 20g, 15g, and 10g of 40wt% NaOH solution were added in three times, and the reaction was continued for 0.5h after each addition of NaOH solution, and finally the reaction was continued at a constant temperature for 1h. The reaction solution was distilled under reduced pressure, isopropanol and excess ECH were recovered, and N2 was added to restore the pressure to normal. After the reaction was completed, the salt residue was separated and removed. Add 200 mL of methyl isobutyl ketone and 25 g of 10% NaOH to a four-necked bottle for further epoxidation dechlorination refining reaction, keep the temperature at 90°C, and react for 2 hours. After the reaction, filter to remove the salt residue, wash with pure water 4 times until neutral, let stand, separate the water layer, and distill under reduced pressure at 150°C to recover methyl isobutyl ketone to obtain a crude PGEE product; then dissolve the crude PGEE product in methyl isobutyl ketone by heating and crystallizing, and then wash the crystal product with n-hexane, and dry at 60°C for 12 hours to obtain 44.59 g of PGEE product, with a yield of 57%.
[0084] The difference between Comparative Example 1 and Example 1 is that the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 26.4wt% of hyperbranched polyimide prepolymer, 6.6wt% of linear polyimide prepolymer, 6wt% of ultrafine aluminum hydroxide in Preparation Example 1, 1wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0085] The difference between Comparative Example 2 and Example 1 is that the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 27.36wt% of hyperbranched polyimide prepolymer, 6.84wt% of linear polyimide prepolymer, 4.8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0086] The difference between Comparative Example 3 and Example 1 is that the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 22.24wt% of hyperbranched polyimide prepolymer, 5.56wt% of linear polyimide prepolymer, 11.2wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0087] The difference between Comparative Example 4 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 31wt% of hyperbranched polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0088] The difference between Comparative Example 5 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 21.7wt% of hyperbranched polyimide prepolymer, 9.3wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0089] The difference between Comparative Example 6 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 29.45wt% of hyperbranched polyimide prepolymer, 1.55wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.0wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0090] The difference between Comparative Example 7 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 25.6wt% of hyperbranched polyimide prepolymer, 6.40wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, and 60wt% of N-methylpyrrolidone.
[0091] The difference between Comparative Example 8 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 25.44wt% of hyperbranched polyimide prepolymer, 6.36wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 0.2wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0092] The difference between Comparative Example 9 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish is made of 24.64wt% of hyperbranched polyimide prepolymer, 6.16wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride with surface hydroxyl modified in Preparation Example 1, 1.2wt% of cross-linking agent - triglycidyl meta-aminophenol, and 60wt% of N-methylpyrrolidone.
[0093] The difference between Comparative Example 10 and Example 1 is that a boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish is made of 24.8wt% of hyperbranched polyimide prepolymer, 6.2wt% of linear polyimide prepolymer, 8wt% of hexagonal boron nitride without surface hydroxyl modification (submicron ultrafine boron nitride powder (average particle size 600nm, CW-BN-002, hexagonal crystal form, Shanghai Chaowei Nano) placed in a planetary ball mill for fine ball milling treatment, ball milling at a speed of 80rpm for 30min), 1.0wt% of a cross-linking agent-triglycidyl m-aminophenol, and 60wt% of N-methylpyrrolidone.
[0094] 1. Thermal weight loss is determined according to the test method of GB / T 27761.
[0095] 2. Thermal conductivity is measured according to GB / T 10297-2015 test method.
[0096] 3. Viscosity is measured according to the test method of GB / T 24148.4-2009.
[0097] 4. Volume resistivity is measured according to GB / T 1981.2-2009 test method.
[0098] 5. The power frequency electrical strength is measured according to the test method of GB / T 1981.2-2009.
[0099] 6. The bonding strength is determined according to the solenoid method in the test method of GB / T 11028-1999.
[0100] Table 1: Test parameter table of high temperature resistant and high thermal conductivity insulating impregnating varnish in Examples 1-22 and Comparative Examples 1-10
[0101] Combining Examples 1-3 and Comparative Examples 1-3 and Table 1, it can be seen that the added mass of the surface-modified hexagonal boron nitride is preferably controlled to be 0.15-0.25 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer, and the surface-modified hexagonal boron nitride, which can ensure good insulation safety performance while having good high temperature resistance and good heat dissipation performance.
[0102] It can be seen from Examples 1, 4-5 and Comparative Examples 4-6 and Table 1 that the anhydride-terminated hyperbranched polyimide prepolymer and the amino-terminated linear polyimide prepolymer can be used in combination to prepare an insulating thermally conductive paint cured product with higher density, but the amount of the linear polyimide prepolymer must be considered. The mass ratio of the hyperbranched polyimide prepolymer to the linear polyimide prepolymer is preferably controlled to be (75-90):(10-25).
[0103] It can be seen from Examples 1, 6-8 and Comparative Examples 7-9 and Table 1 that the amount of cross-linking agent added is preferably controlled to be 0.01-0.025 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride. Too low an amount of cross-linking agent added will affect the density of the insulating thermal conductive paint cured product, thereby causing its high temperature resistance and heat dissipation performance to be significantly reduced. Too high an amount of cross-linking agent added will cause the density of the insulating thermal conductive paint cured product to be too high and easy to crack, affecting the overall service life and safety of use.
[0104] It can be seen from Example 1, Examples 9-20 and Comparative Example 10 and Table 1 that the surface-modified hexagonal boron nitride prepared in the present application can be evenly dispersed in the resin system, thereby ensuring the overall high temperature resistance, insulation safety performance and good heat dissipation performance, while improving the overall mechanical properties and enhancing the service life and safety of the motor.
[0105] It can be seen from Example 1, Examples 9-20 and Comparative Example 10 and Table 1 that the surface modified hexagonal boron nitride obtained by modifying the surface functional groups of CTNs@h-BN ultrafine powder as a carrier can effectively improve the heat dissipation performance and high temperature resistance of the cured insulating thermal conductive paint and ensure the overall power frequency electrical strength ≥22MV / m, which can better meet the timely and efficient heat dissipation and insulation safety requirements of future drive motors.
[0106] It can be seen from Example 1 and Examples 9-20 and Table 1 that the surface hydroxyl-modified CTNs@boron nitride whiskers can be used as a bridging agent for the three-dimensional network thermal conductive channel, which can effectively improve the heat dissipation performance and high temperature resistance of the cured insulating thermal conductive paint and ensure the overall power frequency electrical strength ≥22MV / m, which can better meet the timely and efficient heat dissipation and insulation safety requirements of future drive motors.
[0107] In summary, the insulating impregnating varnish provided by the present invention has a heat resistance grade of up to 200 (C grade) and a thermal conductivity coefficient of ≥0.60 W·m -1 ·K -1 , thermal weight loss (calculated as 5% mass loss) ≥330℃, power frequency electrical strength ≥22MV / m, which can meet the timely and efficient heat dissipation and insulation safety requirements of future drive motors.
[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish, characterized in that: The invention is prepared by thermal imidization or chemical imidization reaction of a hyperbranched polyimide prepolymer, a linear polyimide prepolymer, surface-modified hexagonal boron nitride, a crosslinking agent and a strongly polar aprotic organic solvent; the strongly polar aprotic organic solvent accounts for 55-70wt% of the total high-temperature resistant and high-thermal-conductivity insulating impregnation varnish; the added mass of the surface-modified hexagonal boron nitride is 0.15-0.25 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride; the added mass of the hyperbranched polyimide prepolymer is 0.75-0.90 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer; and the added mass of the crosslinking agent is 0.01-0.025 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
2. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The added mass of the surface-modified hexagonal boron nitride is 0.18-0.22 times the total mass of the hyperbranched polyimide prepolymer, the linear polyimide prepolymer and the surface-modified hexagonal boron nitride.
3. A boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1 or 2, characterized in that: The added mass of the hyperbranched polyimide prepolymer is 0.80-0.85 times the total mass of the linear polyimide prepolymer and the hyperbranched polyimide prepolymer.
4. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The linear polyimide prepolymer is an anhydride-terminated linear polyamic acid PAA or an amino-terminated linear polyamic acid PAA; the anhydride-terminated linear polyamic acid PAA of the linear polyimide prepolymer is prepared from aromatic diamine and aromatic dianhydride; the molar ratio of the aromatic diamine to the aromatic dianhydride is 2:(1.85-2.2); the aromatic diamine is 4,4'-diaminotriphenyl p-phenylenediamine, 4,4'-diaminotriphenylmethane, 3,5-diaminobenzoic acid-4-(4'-butoxy)biphenyl ester, 3,3'-dimethyl-4,4 'Diaminodiphenylmethane, 4,4'-diaminobenzanilide, 2,6-diaminopyridine, 4-phenyl-2,6-bis(4-aminophenyl)pyridine at least one; the aromatic dianhydride is 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2'-bis-(3,4-dicarboxylic anhydride benzene)hexafluoropropane, 3,3',4,4'-bisphenylsulfonetetracarboxylic dianhydride, 3-bromophthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2-diphenyl-4,4',5,5'-biphenyltetracarboxylic dianhydride at least one.
5. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The hyperbranched polyimide prepolymer is an anhydride-terminated hyperbranched polyamic acid HBPAA; the anhydride-terminated hyperbranched polyamic acid HBPAA is prepared from aromatic dianhydride A2 monomer and triamine B3 monomer at a ratio of 2:(3.02-3.05); the molar weights of the aromatic dianhydride A2 monomer and the triamine B3 monomer are; the aromatic dianhydride A2 is 2,2-bis[4-(4-maleimide phenoxy)phenyl]propane, 3,3',4,4'-diphenyl sulfide dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride , at least one of 3,3,4,4-diphenylsulfone tetracarboxylic acid dianhydride; the triamine B3 is at least one of 2,6,14-triaminotriptycene, 2,7,12-triamino-5H-diindole[1,2-a:1',2'-c]fluorene-5,10,15-trione, tris(4-aminophenyl)amine, 1,3,5-tris(4-aminophenoxy)benzene, 4,4',4"-(pyridine-2,4,6-triyl)triphenylamine, and 4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine.
6. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The surface-modified hexagonal boron nitride includes at least one of hydroxylation-modified hexagonal boron nitride, amination-modified hexagonal boron nitride, epoxidation-modified hexagonal boron nitride, epoxidation-modified CTNs@h-BN, amination-modified CTNs@h-BN, and hydroxylation-modified CTNs@h-BN.
7. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 6, characterized in that: The surface-modified hexagonal boron nitride is epoxidation-modified CTNs@h-BN; The preparation method of the surface-modified hexagonal boron nitride is as follows: S1. High temperature activation treatment of h-BN; S2. Weigh 400-600 mL of a 0.02-0.03 mol / L Ag(2E4MI)2Ac complex solution, add 0.5-1.0 parts of CNTs and 0.5-1.0 parts of PVP, disperse by ultrasound for 2-4 hours, add 40-80 parts of h-BN activated in S1, and continue to disperse by ultrasound for 0.5-1.0 hours to obtain a dispersion; S3. The obtained dispersion was subjected to vacuum distillation to remove the organic solvent in the dispersion, and then the solid was sintered at 210-220 ° C for 2-4 hours to obtain a solid; S4. The solid obtained in S3 is ground and crushed by ball milling to obtain CTNs@h-BN ultrafine powder with an average particle size of less than 1000 mesh; S5. The CTNs@h-BN ultrafine powder obtained in S4 is magnetically mixed with a solution of n-butyl lithium, wherein the mass ratio of the n-butyl lithium solution to the CTNs@h-BN ultrafine powder is 1:(50-200), and then an ultrasonic activation reaction is carried out for 1-2 hours. Epichlorohydrin is then added for a nucleophilic substitution reaction, wherein the mass ratio of epichlorohydrin to the CTNs@h-BN ultrafine powder is 1:(4-9). After centrifugation to remove the solvent, the solid product is washed with distilled water and acetone to obtain surface epoxidation-modified CTNs@h-BN.
8. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The surface-modified hexagonal boron nitride is a hyperbranched polyimide graft-modified h-BN ultrafine powder or a hyperbranched polyimide graft-modified CTNs@h-BN ultrafine powder; The preparation method of the surface-modified hexagonal boron nitride is as follows: S1. Preparation of h-BN carrier, the h-BN carrier is h-BN ultrafine powder or CTNs@h-BN ultrafine powder; S2. The h-BN carrier and an aqueous solution of aminosilane with a concentration of 4-8wt% are mixed uniformly in a mass ratio of 1:(10-20), and then ultrasonic dispersion treatment is performed for 1-2h, and then filtered and dried to obtain an aminosilane-modified h-BN carrier; S3. Dispersing the aminosilane-modified h-BN carrier in a highly polar aprotic organic solvent to form a suspension, wherein the content of the aminosilane-modified h-BN carrier in the suspension is 0.5-2wt%; adding ternary anhydride to the suspension, adding triethylamine as a catalyst after sufficient dissolution, heating to 40° C., and reacting for 0.5-1h under ultrasonic dispersion conditions, wherein the amino groups on the surface of the h-BN carrier participate in a nucleophilic addition reaction, and undergo a ring-opening reaction with the anhydride group in the ternary anhydride, wherein at least one anhydride in the ternary anhydride is chemically bonded to the aminosilane-modified h-BN carrier; S4. Adding an aromatic diamine, wherein the molar ratio of the aromatic diamine to the ternary anhydride is 2:(1-1.3), maintaining the temperature at 40° C. and reacting for 12-18 hours under ultrasonic dispersion, and then adding maleic anhydride for end-capping, wherein the molar ratio of maleic anhydride to the aromatic diamine is (0.2-0.5):1, maintaining the temperature at 40° C. and reacting for 8-12 hours under ultrasonic dispersion to obtain an ultrafine polyamic acid HBPAA with h-BN as the core; S5. Add an excess of imidizing agent dropwise into the reaction system, wherein the imidizing agent is a mixture of acetic anhydride and triethylamine in a molar ratio of 1:(0.8-1.2), maintain nitrogen protection, and perform ultrasonic dispersion at room temperature for 8-12 hours to obtain a polymer solution. The obtained polymer solution is precipitated into methanol, stirred and washed, and dried in a vacuum oven for 6-8 hours to obtain hyperbranched polyimide grafted modified h-BN or hyperbranched polyimide grafted modified CTNs@h-BN ultrafine powder.
9. The boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnating varnish according to claim 1, characterized in that: The highly polar aprotic organic solvent is one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and N,N-dimethylformamide; the crosslinking agent is at least one of tetraphenol ethane type epoxy resin, glycidyl ether epoxy resin, hyperbranched polyimide epoxy resin, triglycidyl meta-aminophenol, small molecule diamine, and small molecule triamine.
10. A method for preparing the boron nitride-hyperbranched polyimide high temperature resistant and high thermal conductivity insulating impregnation varnish according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, respectively preparing a hyperbranched polyimide prepolymer, a linear polyimide prepolymer, and a surface-modified hexagonal boron nitride; Step 2: dissolving the hyperbranched polyimide prepolymer, linear polyimide prepolymer and surface-modified hexagonal boron nitride prepared in step 1 in a highly polar aprotic organic solvent, stirring them magnetically and then degassing them in vacuum to obtain a high temperature resistant and highly thermally conductive insulating impregnation varnish material A; Step 3, evenly mix the high temperature resistant and high thermal conductivity insulating impregnating varnish material A and the cross-linking agent material B to obtain a finished high temperature resistant and high thermal conductivity insulating impregnating varnish; The impregnation conditions of the finished product of high-temperature resistant and high-thermal conductive insulating impregnation varnish are as follows: after the motor is impregnated, it is placed in a vacuum oven and maintained at a temperature of 25-40°C for drying for 1-2 hours, and vibrates for 3-5 seconds every 10-30 seconds during the drying period; then the temperature is raised to 160-180°C and maintained for 1-2 hours to heat and remove the organic solvent in the insulating impregnation varnish, and then the temperature is raised to 220-260°C for insulation treatment for 1-2 hours, and finally heated to 240-280°C for heat treatment and curing for 2-6 hours.
Citation Information
Patent Citations
Phosphorus-containing trianhydride monomer and preparation method thereof, polyimide material and preparation method and application thereof
CN118221734A
Hyperbranched polyimide containing alkynyl group, and preparation method and application thereof
CN105037724A
Modified polypropylene / hyper branched polyimide insulated alloy material and preparation method thereof
CN105153620A
Graphene grafting modified hyperbranched polyimide dielectric material and preparation method thereof
CN112898587A
Insulating base material-carbon nanotube hybrid material and preparation method and application thereof
CN113754925A